Toxicity of gold nanoparticles (AuNPs): A review - Sani, A.; Cao, C.; Cui, D. (Biochemistry and biophysics reports, 2021)
Gold nanoparticles are a kind of nanomaterials that have received great interest in field of biomedicine due to their electrical, mechanical, thermal, chemical and optical properties. With these great potentials came the consequence of their interaction with biological tissues and molecules which presents the possibility of toxicity. This paper aims to consolidate and bring forward the studies performed that evaluate the toxicological aspect of AuNPs which were categorized into in vivo and in vitro studies. Both indicate to some extent oxidative damage to tissues and cell lines used in vivo and in vitro respectively with the liver, spleen and kidney most affected. The outcome of these review showed small controversy but however, the primary toxicity and its extent is collectively determined by the characteristics, preparations and physicochemical properties of the NPs. Some studies have shown that AuNPs are not toxic, though many other studies contradict this statement. In order to have a holistic inference, more studies are required that will focus on characterization of NPs and changes of physical properties before and after treatment with biological media. So also, they should incorporate controlled experiment which includes supernatant control Since most studies dwell on citrate or CTAB-capped AuNPs, there is the need to evaluate the toxicity and pharmacokinetics of functionalized AuNPs with their surface composition which in turn affects their toxicity. Functionalizing the NPs surface with more peculiar ligands would however help regulate and detoxify the uptake of these NPs. •In vitro and in vivo indicate oxidative damage to tissues and cell lines.•The liver, spleen and kidney tissues and cells were most affected.•Some controversy exist, however, the primary toxicity is collectively determined by the properties of the NPs.•Characterization of NPs and changes in physicochemistry before and after treatment with bio-media should be evaluated.•Functionalizing the NPs surface with more peculiar ligands would help regulate and detoxify the uptake of these NPs.